Online Lending and Debt Dependency Patterns among Residents of Teluk Langkap Village, Sumay District, Tebo Regency - Regi Kurniawan; Muhammad Pauzi; Nazori; Neneng Sudharyati (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although online lending has expanded financial inclusion by providing accessible and rapid financing, its increasing use has also raised concerns regarding debt dependency, particularly among rural communities characterized by limited financial literacy and unstable economic conditions. This study aims to investigate the use of online lending among residents of Teluk Langkap Village, Sumay District, Tebo Regency, and to analyze the factors contributing to the development of debt dependency. A qualitative descriptive approach with field research was employed. Informants were selected through purposive sampling and comprised online lending users and village officials. Data were collected through observations, in-depth interviews, and documentation and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, while data trustworthiness was assessed through confirmability. The findings reveal that online lending is primarily used to meet urgent economic needs because of its accessibility, simple application procedures, and rapid disbursement. However, its use has increasingly extended to consumptive purposes and routine household expenditures, contributing to repeated borrowing practices. Debt dependency is driven mainly by imbalances between household income and expenditure, inadequate financial literacy, limited financial management capabilities, and a lack of alternative financing sources, resulting in recurring borrowing to repay previous debts. The study concludes that online lending dependency is shaped by interconnected economic, technological, and behavioral factors. These findings contribute to the literature on Islamic economics, digital finance, and financial behavior by illustrating how structural and individual vulnerabilities interact in rural online lending practices. The study also highlights the importance of strengthening financial literacy, responsible household financial management, and access to appropriate financing alternatives to reduce the risk of persistent debt dependency.